Rectal and Intranasal Immunizations with Recombinant Urease Induce Distinct Local and Serum Immune Responses in Mice and Protect against Helicobacter pylori Infection - Kleanthous, Harry (American Society for Microbiology, 1998)
To determine the optimal inductive sites for immunization against Helicobacter pylori infection, the protective efficacy of recombinant urease (rUre) was assessed for mice given the vaccine by either the oral (p.o.), intranasal (i.n.), or rectal route. When mice were immunized with rUre (25 μg p.o. or rectally or 10 μg i.n.) plus heat-labile toxin from Escherichia coli as the mucosal adjuvant, all routes afforded protection against challenge with H. pylori, as indicated by a significant reduction in gastric urease activity (P < 0.0005) compared to that of sham-immunized controls. Quantitative H. pylori culture of stomach tissue demonstrated a >97% reduction in bacterial burden in mice immunized by all routes (P < 0.05). Induction of antiurease immunoglobulin A (IgA) levels in gastric luminal secretions after p.o. immunization was greater than after i.n. administration (means, 6.0 and 1.02 ng/ml, respectively) and was dependent upon challenge with H. pylori. However, immunization by the rectal route resulted in the generation of the highest levels of gastric antiurease IgA (mean, 40.89 ng/ml), which was detectable prior to challenge with H. pylori. Immunohistochemical staining of stomach tissue for cells secreting urease-specific antibody and CD4(+) T cells showed levels of recruitment to be dependent upon challenge with H. pylori and equivalent for all routes. These results identify both the rectum and nasal passages as suitable inductive sites for urease immunization.